1999
DOI: 10.1089/10430349950018490
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evaluation of Biopsy and Autopsy Specimens from Patients Receiving in Vivo Retroviral Gene Therapy

Abstract: We used the polymerase chain reaction (PCR) to assay for the presence of retroviral vector and replication-competent retrovirus (RCR) in autopsy and biopsy specimens from patients who received inoculations of retroviral vector producer cells (VPCs) into brain tumors or apparently normal tissues surrounding resected tumors. The PCR assays were capable of detecting 1 or more proviral copies of vector or RCR in 500,000 cells. Of 113 patients treated in clinical trials between 1994 and 1997, autopsy specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…[31][32][33] with recurrent GBM caused a strong systemic cellular immune response with major intratumoral infiltrates of immunocompetent cells. 18 In tumor specimens taken a week after VPC injection, strong macrophage infiltration and perivascular lymphocytic accumulation were observed.…”
Section: Figure 2 Facs Immunophenotyping Of Peripheral Lymphocytes Inmentioning
confidence: 99%
“…[31][32][33] with recurrent GBM caused a strong systemic cellular immune response with major intratumoral infiltrates of immunocompetent cells. 18 In tumor specimens taken a week after VPC injection, strong macrophage infiltration and perivascular lymphocytic accumulation were observed.…”
Section: Figure 2 Facs Immunophenotyping Of Peripheral Lymphocytes Inmentioning
confidence: 99%
“…8 Vector sequences have also been detected in autopsy specimens from brain tissue, liver, kidney and lung specimens. 9 Importantly, in these studies, vector sequences have not been detected in any gonadal specimens from 22 patients (10 female; 12 male) evaluated to date. While these clinical data are reassuring, the limited sample size does not provide sufficient information for determining the potential risk of vector distribution to unintended tissues and organs.…”
Section: Introductionmentioning
confidence: 83%
“…Indeed, it has been shown that even when therapeutic vectors are delivered locally to a primary tumor, systemic effects still occur, indicating that the vector has become bloodborne. 32,33 One approach to circumvent this problem is through the use of elements allowing specific transcriptional regulation of the vector, e.g., the use of tissuespecific promoters 3 and inducible promoters. 4 Whereas these approaches are very promising, they require specific knowledge of the cancer cells, and are not applicable to most situations.…”
Section: Discussionmentioning
confidence: 99%